CIVIL IDENTIFICATION WITH DNA PROFILES DATABASES USING BAYESIAN NETWORKS - Andrade, Marina; Ferreira, Manuel Alberto M. (Acta Scientiae et Intellectus, 2024)
In forensic identification problems it is common the use of DNA profiles. The first bases of DNA profiling data emerged in England in 1995 having raised new challenges in the context of forensic identification. In Portugal the legislation that allowed the creation of a DNA profile database was set in 2008. In this work it is intended to discuss how to properly use the databases in the recognition of bodies problem that compiles information about missing individuals which are known to belong to one or more families whose members have reported the disappearance of relatives.